High-quality resonances in terahertz composite slabs based on metal gratings. (1st October 2022) - Liu, Dejun; Yu, Xi; Wu, Feng; Cao, Jun; Zhao, Yanliang; Shi, Hui; Xiao, Shuyuan; Kuwahara, Makoto; Itoigawa, Fumihiro; Ono, Shingo; Chen, Lin; Liu, Feng
Abstract: In this study, a terahertz (THz) composite slab (TCS) based on metal grating and dielectric films is experimentally and numerically investigated in the THz region. By combining a dielectric film, the TCS exhibits different sharp resonances for varied polarization waves. A sharp Fano resonance is excited for transverse magnetic (TM) waves, which originates from the introduced asymmetric factor by dielectric films. The film thickness and refractive index can be used for the Fano resonance tuning. The resonant Q -factor can be improved using thinner and lower refractive index films. For transverse electric (TE) modes, a resonance termed guided modes can also be induced when the dielectric film is thick enough. The effects of film thickness and refractive index on these resonances are analyzed in detail. These results demonstrated that this TCS with high Q -factors or narrow resonances for both TM and TE waves is a promising component for THz filter and sensor applications.